Radicalism as Issued in Online Media: A Discourse Analysis - Adriansyah Abu Katili (Univeristas Negeri Gorontalo, 2022)
This is the discourse analysis of the text of radicalism. The analysis is aimed at how the texts issue radicalism. The data are obtained from the internet. They were analyzed by applying the theory of relevance developed by Sperber and Wilson. The research shows that the texts contain explicature, higher-level explicature, and implicature. The research shows that the texts implied the accusing Islam the religion of radicalism and that Muslims are a radical group of people.